Parents and Teacher Communication Patterns in Increasing Learning Interest in Students of Madrasah Aliyah Negeri 2 Labuhanbatu Utara during the Covid-19 Pandemic - Rahmad Jainuri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to look at the communication patterns of parents and teachers in increasing student interest in learning at Madrasah Aliyah Negeri 2 Labuhanbatu Utara, where the presence of the covid-19 pandemic has an impact on the order of life, including in the world of education, which results in changing the learning formulation from face to face (offline) to study at home (online), so that not a few students experience boredom due to this. The results of the study indicate that the objective conditions of student interest in learning XI IPA V MAN 2 Labuhanbatu Utara obtained data from 39 students who filled out the form, there were 37 students or 95% of students who felt bored following online learning. Meanwhile, 2 people or 5% were still in a relaxed state or did not experience boredom when participating in online learning. That from this boredom, communication between parents and teachers does not work effectively, where the communication pattern that is built is a primary and secondary communication pattern that is carried out using telecommunications connected using the theory of social penetration. The lack of good communication between teachers and parents certainly has an inhibiting factor. The inhibiting factor from the parent's side is the busyness of parents, the condition of parents who are less attentive to their children at home, but there are other things that become the inhibiting factor, namely the ability of parents to communicate less, where parents are not good at communicating so there is always a feeling of fear or inferiority to start communication first. Meanwhile, the inhibiting factor from the teacher's side is the busyness of the teacher because in addition to teaching the teacher also has to take care of the household, and there is no good response from parents.